Unveiling The Mediating Effect Of Organizational Commitment In The Quality Of Work Life To Performance Nexus - Rama Fajar Shidiq; Muhammad Zain Alfain; Vitradesie Noekent (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research examines the influence of Quality of Work Life (QWL) on Employee Performance (EP), with Organizational Commitment (OC) serving as a mediating factor. A quantitative approach was employed, utilizing SEM-PLS, and drawing data from a sample of 211 employees at PT Asia Pacific Fibers Kendal. The findings reveal that QWL significantly and positively affects both Employee Performance (EP) and Organizational Commitment (OC). Additionally, Organizational Commitment (OC) has a notable positive impact on Employee Performance (EP). The study highlights the critical role of QWL in fostering a productive and fulfilling work environment. It recommends future research to explore different variables or indicators to further investigate the role of OC, as well as expanding the sample size and diversity for more comprehensive insights